2009
DOI: 10.1161/strokeaha.109.563692
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Vascular Malformations of the Brain

Abstract: Background and Purpose-This review discusses recent research on the genetic, molecular, cellular, and developmental mechanisms underlying the etiology of vascular malformations of the brain (VMBs), including cerebral cavernous malformation, sporadic brain arteriovenous malformation, and the arteriovenous malformations of hereditary hemorrhagic telangiectasia. Summary of Review-The identification of gene mutations and genetic risk factors associated with cerebral cavernous malformation, hereditary hemorrhagic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
122
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(132 citation statements)
references
References 95 publications
0
122
0
3
Order By: Relevance
“…19,20,22 Studies of AVM tissue have shown increased endothelial cell proliferation and increased expression of angiopoietin-2 and vascular endothelial growth factor, which promote vascular destabilization and proliferation, respectively. 17 However, the exact triggering event that leads to increased and disorganized angiogenesis ultimately leading to AVM formation has not been identified.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…19,20,22 Studies of AVM tissue have shown increased endothelial cell proliferation and increased expression of angiopoietin-2 and vascular endothelial growth factor, which promote vascular destabilization and proliferation, respectively. 17 However, the exact triggering event that leads to increased and disorganized angiogenesis ultimately leading to AVM formation has not been identified.…”
mentioning
confidence: 99%
“…8 This finding suggests that the presence of a genetic abnormality alone is not enough to trigger AVM formation and a "second hit" is required. 22 A possible mechanism to explain AVM formation may not be dissimilar to that responsible for dural arteriovenous fistulas-that is, venous thrombosis leading to impaired venous outflow, ischemia, and increased angiogenesis. 1 In the case of brain AVMs, asymptomatic parenchymal venous thrombosis could trigger local venous hypertension and ischemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47] Homozygous loss of these genes leads to death in utero. 48 ENG and ALK1 are expressed on ECs and bind TGF-β, modulating EC proliferation, migration, adhesion, and apoptosis. 49 They are downregulated during adulthood, but are reactivated when the need for vascular repair arises.…”
Section: Endoglin and Its Role In Inflammation And Vascular Remodelingmentioning
confidence: 99%
“…Owing to the extensive involvement of ENG and ALK1 in maintaining vascular stability, missing an allele and thus expressing lower amounts of these proteins leads to vascular dysmorphogenesis and potentially hemorrhage. 48 As part of the TGF-β receptor complex, ENG is also involved in the neovascularization of damaged tissue during inflammation. It binds activated circulating leukocytes, enabling them to adhere to damaged endothelium or ischemic tissues.…”
Section: Endoglin and Its Role In Inflammation And Vascular Remodelingmentioning
confidence: 99%